2000
DOI: 10.1046/j.1464-410x.2000.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

The significance of serum levels of insulin‐like growth factor‐1 in patients with prostate cancer

Abstract: Objectives To compare the serum levels of insulin-like growth factor-1 (IGF-1) in patients with prostate cancer and in control patients with no malignancy, and to evaluate any possible in¯uence of testicular androgen withdrawal on the level of IGF-1 in patients with prostate cancer. Patients and methods IGF-1 was measured in serum samples from 238 patients using both a chemiluminescence method and a radio-immunoassay. From a subgroup of 19 patients presenting with newly diagnosed carcinoma of the prostate, IGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…Chan et al (32) reported an association between serum IGF-I levels and the risk of prostate cancer. However, in other studies, a direct correlation between prostate cancer and serum IGF-I could not be found (33,34). IGF-II also plays a critical role in the autocrine and paracrine stimulation of prostatic neoplasms.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Chan et al (32) reported an association between serum IGF-I levels and the risk of prostate cancer. However, in other studies, a direct correlation between prostate cancer and serum IGF-I could not be found (33,34). IGF-II also plays a critical role in the autocrine and paracrine stimulation of prostatic neoplasms.…”
Section: Discussionmentioning
confidence: 78%
“…There is a lack of consensus regarding the influence of IGF-I on the etiology of prostate cancer (29)(30)(31)(32)(33)(34). Chan et al (32) reported an association between serum IGF-I levels and the risk of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, a growing body of evidence suggests that serum insulin-like growth factor 1 (IGF-1) and insulin-like growth factor binding protein-3 (IGFBP-3) levels may play a role in prostate cancer risk and/or severity (5,6). Previous findings relating circulating levels of IGF-1 and IGFBP-3 to prostate cancer risk and severity have been intriguing, although not entirely consistent (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Of note, a positive association between increased IGF-1 levels and prostate cancer was found in three prospective studies (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that IGF-I levels were higher in prostate cancer patients than in the control subjects (Cohen, 1993;Ho and Baxter, 1997;Mantzoros et al, 1997;Chan et al, 1998;Wolk et al, 1998;Djavan et al, 1999;Signorello et al, 1999;Stattin et al, 2000;Harman et al 2000), whereas others showed the opposite (Kanety et al, 1993;Finne et al, 2000;Kurek et al, 2000).…”
mentioning
confidence: 97%